Interdisciplinarity in Transdisciplinary Projects: Circulating Knowledges, Practices and Effects. Issue 2 (3rd April 2018) - Holmes, Helen; Gregson, Nicky; Watson, Matt; Buckley, Alastair; Chiles, Prue; Krzywoszynska, Anna; Maywin, Jose
Abstract: This article argues that the emphasis on solving substantive "real-world" problems through interdisciplinary research collaboration can neglect the wider value created by such collaborations. Championing the role of a knowledge integration and reflection facilitator, the article contends that more recognition be given to the value of "spillover" effects associated with interdisciplinary modes of working, rather than focusing solely on knowledge outputs and impacts. Drawing on embedded research conducted in relation to a project on local energy futures involving physicists, architects and geographers, the paper illustrates such "spillover" in relation to academic practice in teaching, project management and research methods. Such "spillovers" signal that what travels in interdisciplinary working is much more than formal knowledge and point to potential long-term legacy effects from interdisciplinary working occurring back in the disciplines.